2021
DOI: 10.21203/rs.3.rs-595148/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMC4, CCNB1 and CKS1B as potential targets and new critical biomarkers for the prognosis of human bladder cancer

Abstract: Background As a common malignant cancer of the urinary system, the precise molecular mechanisms of bladder cancer remain to be illuminated. The purpose of this study was to identify core genes with prognostic value as potential oncogenes for the diagnosis, prognosis or novel therapeutic targets of bladder cancer. Methods The gene expression profiles GSE3167 and GSE7476 were available from the Gene Expression Omnibus (GEO) database. Next, PPI network was built to filter the hub gene through the STRING databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Numerous studies have reported that CCNB1 is overexpressed in many tumorshepatocellular carcinoma (27), colon cancer (28), and pancreatic cancer (29)-and promotes tumor cell proliferation. A recent study identified CCNB1 as a potential target and a new key biomarker for the prognosis of human BCa (30); this study's results confirm this. In cell cycle progression, CDC20 is an important control factor of cell cycle checkpoints.…”
Section: Discussionsupporting
confidence: 84%
“…Numerous studies have reported that CCNB1 is overexpressed in many tumorshepatocellular carcinoma (27), colon cancer (28), and pancreatic cancer (29)-and promotes tumor cell proliferation. A recent study identified CCNB1 as a potential target and a new key biomarker for the prognosis of human BCa (30); this study's results confirm this. In cell cycle progression, CDC20 is an important control factor of cell cycle checkpoints.…”
Section: Discussionsupporting
confidence: 84%